Learning Multiplication Using Indonesian Traditional game in Third Grade - Prahmana, Rully Charitas Indra; Zulkardi, Zulkakrdi; Hartono, Yusuf (IndoMS Pusat, 2012)
Several previous researches showed that students had difficulty in understanding the basic concept of multiplication.Â Students are more likely to be introduced by using formula without involving the concept itself. This underlies the researcher to design a learning trajectory of learning multiplication using Permainan Tradisional Tepuk Bergambar (PT2B) as a context based on the student experience. The purpose of this research is to look at the role of PT2B in helping students understanding in learning multiplication, which evolved from the informal to formal level in third grade with Pendidikan Matematika Realistik Indonesia (PMRI) approach. The method used is design research starting from preliminary design, teaching experiments, and retrospective analysis. This research describes how PT2B make a real contribution to the third grade students of SDN 179 Palembang to understand the concept of multiplication. The results showed PT2B context can stimulate students to understand theirÂ knowledge of the multiplication concept. The whole strategy and model that students discover, describe, and discuss shows how the students construction or contribution can uses to help their initial understanding of that concept. The stages in the learning trajectory of student have an important role in understanding the concept of the operation number from informal to the formal level. Â Keyword: Design Research, PMRI, Multiplication, Permainan Tradisional Tepuk Bergambar